Situation Report: Hungary, 30 May 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. What Kadar Did Not Say on Radio and Television / by Alfred Reisch The "Fight for Peace" Continue / by Judith Pataki Unemployment or Subsidized Labor Regrouping? / by Eva Lengyel Diesel Trains Bring New Zealand Prime Minister to Hungary / by Alfred Reisch Hungary and Zimbabwe to Expand Relations following Mugabe's Visit / by Alfred Reisch Greek Prime Minister's Visit Yields Economic Cooperation Agreement / by Alfred Reisch Editorial Board of Hungarian Journal in Yugoslavia Dismissed / by Slobodan Stankovic Belgrade Weekly's Explanation of the Dismissals / by Slobodan Stankovic